2019
DOI: 10.1002/jmri.26975
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Reporting of a Unique Biparametric MRI: Towards Biparametric MRI‐Based Nomograms for Prediction of Prostate Biopsy Outcome in Men With a Clinical Suspicion of Prostate Cancer (IMPROD and MULTI‐IMPROD Trials)

Abstract: Background: Multiparametric MRI of the prostate has been shown to improve the risk stratification of men with an elevated prostate-specific antigen (PSA). However, long acquisition time, high cost, and inter-center/reader variability of a routine prostate multiparametric MRI limit its wider adoption. Purpose: To develop and validate nomograms based on unique rapid biparametric MRI (bpMRI) qualitative and quantitative derived variables for prediction of clinically significant cancer (SPCa). Study Type: Retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Additionally, in patients with positive MRI, two to four extra target cores were taken from each suspicious lesion. The data sets were restricted to men with a PSA value of <20 ng/ml and no prior diagnosis of PCa; thus, the included final population may differ from that in prior publications, which included some men from these cohorts [2,4,17].…”
Section: Biopsy Cohortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in patients with positive MRI, two to four extra target cores were taken from each suspicious lesion. The data sets were restricted to men with a PSA value of <20 ng/ml and no prior diagnosis of PCa; thus, the included final population may differ from that in prior publications, which included some men from these cohorts [2,4,17].…”
Section: Biopsy Cohortsmentioning
confidence: 99%
“…Such an approach binds the decision to perform biopsy to the clinical suspicion of PCa to be determined using MRI, risk calculators, and biomarkers [1]. While several risk calculators and biomarkers have been developed and are currently under evaluation [2][3][4], the "MRI pathway" is supported by level 1 evidence, but seems to be limited by the low to moderate inter-reader and -center reproducibility and the low specificity/positive predictive value (PPV) [5][6][7]. Studies have shown that omitting biopsies in patients with no lesion on MRI would miss up to 5-11% of all csPCa cases (ISUP grade >2) [5,8], whereas performing biopsy in all patients with an equivocal MRI finding (PI-RADS 3 lesions considered to be positive by guidelines [9]) can result in a diagnosis of csPCa in 3-50% of the patients [5,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Having said this, additional external validation studies in different biopsy settings are warranted since the clinical utility of these models could be cohort dependent. It is also worth mentioning that calculators including mpMRI, though outperforming the mpMRI naïve ones, involve obtaining mpMRI in all patients and this may not be afforded in centers with limited resources ( 28 ). Conversely, mpMRI naïve RCs offer the unique opportunity to potentially tailor further testing, such as mpMRI and PBx itself, on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, Magnetic Resonance Imaging (MRI) is increasingly used in the diagnostic pathways for prostate cancer (PCa). Simplified MRI protocols with shorter acquisition time and with no use of contrast agents (biparametric MRI) hold the promise to further reduce costs of prostate imaging and promote its use in any patient at risk of PCa [1,2]. Furthermore, compared to other tools such as biomarkers, prostate MRI allows to characterize and localize PCa lesions and to eventually perform targeted biopsy of any suspicious lesions.…”
Section: Introductionmentioning
confidence: 99%